Assessing, synthesizing and categorizing the technical requirements for service quality improvement: an exploratory study on Islamic banks in Bangladesh / Muhummad Khairul Islam ... [et al.] - Islam, Muhummad Khairul; Hoque, Muhammad Nazmul; Islam, Rafikul; Khanom, Fahima (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2025)
The aim of this study was to identify the technical requirements of Islamic banks in Bangladesh for fulfilling the needs and requirements from their customers to ensure service quality. Data were collected through interviews as one of the “generic qualitative inquiry” approach from 25 middle and top level of executives who have had at least five years of experience in dealing with their valued customers from seven Islamic banks on a personal contact basis. The research data were analyzed starting with transcribing the statements of respondents and later the analysis was completed through content analysis. Altogether, 47 synthesized technical requirements (how’s) were developed and later, all the requirements were categorized under 6 dimensions namely, Employees’’ Competency, Islamic Shariah Matters, Service Quality Practice, HRD and Management Role, TQM Practice, Communications and Information Technology. The findings of this research provided the plausible and necessary guidelines to the executives of Islamic banks in Bangladesh for fulfilling the needs and expectations to build customer satisfaction and attain competitive advantage through the service quality enhancement. Moreover, this study provides new insights into customers’ technical requirements about Islamic banking services that could assist those banks to understand the customers’ perceptions for upholding the ultimate satisfaction.